Characterization of the deformation bands in AA1100 deformed by plane forging and return-plane forging - Min-Seong Kim; Jeong Gyun Kim; Sang-Chul Kwon; Sun-Tae Kim; Hwan-Uk Guim; Seong Lee; Hyo-Tae Jeong; Shi-Hoon Choi (Journal of Materials Research and Technology, 2022)
In this study, the deformation bands (DBs) in AA1100 after plane forging (PF) and return-plane forging (R-PF) during multi-axis diagonal forging (MADF) were observed using microtexture analysis. Typical texture components (plane-strain texture components) observed in face-centered cubic (FCC) materials deformed by plane-strain compression were developed in the PF specimen. Blurry bands with an orientation relationship of mainly LAGBs were developed in the deformed grains in the PF specimen. Slip trace analysis and Schmid factor (SF) calculations revealed the correlation between the blurry bands and the slip behavior. Regions of matrix and DBs inside the deformed grains of the R-PF specimen were distinguished mostly by their HAGBs. The heterogeneity of the Taylor factor (M) values that occurred within the blurry bands and their surrounding regions induced the development of the DBs in the R-PF specimen. The heterogeneities of the deformation behavior between the inside and the outside of the blurry bands that developed in the grains of the PF specimen during the R-PF were a direct reason for the generation of DBs in the deformed grains of the R-PF specimen. The transmission-EBSD (t-EBSD) technique revealed that the average misorientation angle inside the DBs was higher than that inside the matrix.